Ground water quality assessment and its impact with special reference to Chhindwara District of Madhya Pradesh, India - Neelima Bagde (International Journal of Life Sciences, 2016)
The Earth is full of natural resource needed for the development of mankind. The day by day increased demand has developed new methods of water quality assessment and management. The study was carried out for the ground water quality assessment of 9 Tahsil/Blocks of Chhindwara district. Water is the basic resource for sustaining all human activities, so its provision in desire quantity and quality is most important. For assessment of water quality of the district were selected Junnardeo, Chhindwara, Chourai, Tamia and Pandhurna. Samples of ground water were collected from 5 blocks of the affected area and analyzed for physico chemical parameters like pH, Electrical conductivity, alkalinity, total hardness, fluoride ion were analyzed. Some water sample show higher fluoride ion concentration, higher turbidity. Over all some parts of bore well/tube well water and hand pump water needed treatment for drinking purpose due to hardness and fluoride are present in desirable limit. The present study is focused on measuring the quality of ground water in rural areas of Chhindwara district and its effect on human health. The sample were found to have high pH, indicating alkalinity, high fluoride concentration is mainly found in Tamia, Chhindwara, Jamai, Pandhurna and Chaurai on the contrary these findings, majority of people living in these areas were suffering from fluoride related disease, so the study argues about the need of proper analysis and importance of water treatment and management system in current times